PROBLEMS OF PUBLIC DEBT MANAGEMENT SYSTEM IN RUSSIA - S. E. Tsvirko (Real Economics Publishing House, 2014)
The problems of the Russia’s debt management are revealed. Evolution of the public debts’ problem of the Russian Federation including the question of its interaction with private debts is discussed. Risks in debt sphere are analyzed. Specific features of the Russian economy such as the dependence on world energy prices, low efficiency of public expenditures, rapid growth of internal public debts and external quasi-sovereign and private debts are defined. Principles of debt management and areas of improvement in the system of Russia’s debt management were defined.